Working with women who use force: a feasibility study protocol of the Positive (+)SHIFT group work programme in Australia. Issue 5 (6th May 2019) - Kertesz, Margaret; Humphreys, Cathy; Larance, Lisa Young; Vicary, Dave; Spiteri-Staines, Anneliese; Ovenden, Georgia
Abstract : Introduction: This study assesses the feasibility of the Positive Shift (+SHIFT) programme in the context of legal responses and social welfare provision in the state of Victoria, Australia. The +SHIFT programme, adapted from the Vista curriculum, is a group work and case management programme for women who use force. Building on traditional survivor support group strengths, the programme facilitates participants' engagement with viable alternatives to force while promoting healing. The study also aims to increase understanding about the characteristics and needs of women who use force in Australia. Methods and analysis: This feasibility study will assess the +SHIFT programme's appropriateness in addressing women's use of force in the Victorian context. Process evaluation will be undertaken to identify recruitment, retention, women's participation, barriers to implementation, the appropriateness of proposed outcome measures and other issues. The feasibility of an outcome evaluation which would employ a longitudinal mixed methods design with measures administered at preprogramme, programme completion and 3 months postprogramme time points, along with semistructured interviews with participants, programme staff and referring professionals, will also be assessed. Ethics and dissemination: Research ethics approval was obtained from the University of Melbourne Human Research Ethics Committee. Results of the study will be communicated to the programme providers as part of the action research process evaluation methodology. On completion, final results will be reported to programme providers and funding bodies, and published in academic journals and presented at national and international conferences.